Exploring the Efficacy of Vegetarian Diet in Diverse Pathologies - Puchalski, Krzysztof; Szumlas, Zuzanna; Mrozek, Łukasz; Hajduk, Aleksandra; Jurek, Aleksander; Klocek, Konrad; Zwolski, Maciej; Kostecki, Bartosz; Witalec, Szymon (Journal of Education, Health and Sport, 2023)
Introduction and Purpose: Human health is influenced by a variety of factors, such as genetics, environment, lifestyle, and accessibility to healthcare. While some of these factors are beyond the control of the patient, lifestyle, which is considered the primary determinant of a healthy life, strongly relies on individual choices. In this paper, we aim to demonstrate the benefits of adopting a vegetarian diet as a cornerstone for maintaining good health and as a supplementary approach to treating common diseases.State of Knowledge: The vegetarian diet is primarily based on plants and includes products from animals, such as eggs and dairy. However, it excludes all types of meat and any products that require the death of animals. This diet is adopted for various reasons, including religious, socio-economic, or ethical considerations. It is recognized globally and has become a subject of scientific research for numerous scholars. Many studies investigate its influence on human health, and the results are generally positive. The diet is frequently used as a treatment, often in combination with specific pharmaceutical drugs. This approach leads to weight reduction, decreases the risk of cardiovascular diseases, and can have positive therapeutic effects on conditions like gout or chronic kidney disease. Given that some of these diseases have become increasingly problematic for public health systems, a vegetarian diet can help decrease the number of people affected by them.Conclusion: Given that cardiovascular diseases and incidents are the leading causes of death worldwide, adopting a vegetarian diet can assist patients in avoiding them by reducing their LDL levels and decreasing blood pressure. This diet demonstrates a positive therapeutic effect on patients dealing with chronic kidney disease and gout. It aids in weight reduction and helps prevent the development of metabolic syndrome, which has a variety of beneficial effects.